Os ideais da reforma urbana na legislação e na prática governamental em Belo Horizonte, Minas Gerais - Carolina Helena Miranda e Souza (2016)
This masters thesis presents the translation of the ideals existent in proposals for an Urban Reform in Brazil into legislation and practices in the city of Belo Horizonte. We begin with a brief history of Brazil and Belo Horizontes urbanization from the early twentieth century, pointing out the main features of this process. Among these characteristics, we emphasize the accelerated process of urbanization in the second half of the century, the burst of urban social movements and the first proposals for an Urban Reform, developed in the 1960 decade. Since then, these proposals have been transforming and incorporating new concepts, through the 1980s democratization movements to the most contemporary settings, related to the right to the city. In this process, it is possible to register progress as the incorporation of the Urban Policy chapter of the 1988 Federal Constitution and the approval of the City Statute in 2001, both examples of the legislative field. The definition of the Urban Reform expression headed for more abstract concepts and use, currently, urban policy instruments to pursue its implementation. The history of these instruments dates back to the 1960s demands. Changes, insertion and removal of laws projects marked this process, gaining ground gradually in municipal practices. Today, urban policy instruments are essential tools for achieving the ideals embraced by various concepts of Urban Reform. In addition to the bibliographical and documentary research, another methodology used was qualitative research by interviews with people who were involved with aspects of Belo Horizontes urban policy. We seek to represent different points of view by interviewing technicians, academics, politicians, and people involved in newer and older processes. The interviews were about what they understand by Urban Reform and what they consider as developments, regressions and possibilities in this area, especially about the municipal scene. This allowed to aggregate reports based on practical experience of the interviewed and to compare these results with the literature and document review, which resulted in a characterization of the main aspects of issues related to Urban Reform in Belo Horizonte.